TEAT FISTULA IN A JAMUNAPARI GOAT - A CASE REPORT - Deepak Kumar Kashyap; Devesh Kumar Giri; Govina Dewangan (Exploratory Animal and Medical Research, 2017)
A four years old Jamunapari goat was brought with the history of teat injury at left quarter with leaking of fresh milk from the site and blocked right quarter. Clinical examination showed fistulous opening on the mid region of left quarter. Infant feeding tube was placed in the both quarters. Milk drained out and three-layer closure was performed using no. 3-0 PGA and skin sutured with silk. Postoperatively, antibiotic and analgesic with local infusion were given. The animal showed complete recovery on 15 th day without any complications.